Gender, masculinities and lifelong learning - Bowl, Marion (London ; New York : Routledge, 2012)
"If feminism is still an ongoing project after 60-odd years, then why has the backlash been so long in the coming? This edited volume reflects on current debate around gender in education, where academics, practitioners and policy-makers are beginning to refer to a crisis of masculinity. Why is there an under-representation of men in education? Why do women increasingly outstrip men in terms of achievement? Is it possible men are becoming educationally disadvantaged?Drawing on research from the UK, Australia, New Zealand and Canada the contributors reveal the full spectrum of issues at hand in gender inequality in education. Other forces which have comparable impacts, and which intersect with gender include class, ethnicity and age as well as colonisation. In the light of this, the book provides both evidence and argument to illuminate contemporary debates about the involvement of women and men in education. Importantly, this book critically addresses some of the taken-for-granted beliefs about men and their engagement in lifelong learning, presenting new evidence to demonstrate the complexity of gender and education today. With these complexities in mind, the authors develop new frameworks and questions which provide a theoretical basis to develop further understanding of the many issues involve with gender and lifelong learning.This book will be of interest to any practitioner open to the fresh ideas and approaches in teaching and programming needed when taking into account the differences both between men and women and among men and women"--
pt. 1. Concepts, theories and current debates -- pt. 2. Changing discourses and images -- pt. 3. Gender, masculinities and learning in the life course -- pt. 4. Implications.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Adult education -- Social aspects -- Cross-cultural studies; Continuing education -- Social aspects -- Cross-cultural studies; Sex differences in education -- Cross-cultural studies; Men -- Identity -- Cross-cultural studies; Underachievement -- Cross-cultural studies; Electronic books